Synergistic, Attenuative and Modulatory activity in Dimethylnitrosamine (DMN)-induced fibrotic rats treated with Vernonia amygdalina and Annona muricata leaves - Usunomena, Usunobun; Okolie, Ngozi Paulinus (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
This study assessed the effect of Vernonia amygdalina and Annona muricata leaves on oxidative stress and extracellular matrix induced by dimethylnitrosamine (DMN) - induced liver fibrosis. Control group received physiological saline; Second group received 100mg/kg each of Vernonia amygdalina and Annona muricata ethanol leaf extract without DMN orally for 14 consecutive days. Third group received 10mg DMN/kg (intraperitoneally) thrice weekly for two weeks, in addition to 100mg/kg each of Vernonia amygdalina and Annona muricata administered for 14 days consecutively while the last group received only 10mg DMN/kg. At the end of administration, the rats were sacrificed, blood samples collected and sera analysed for hyaluronic acid (HA), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), alanine transaminase (ALT), aspartate transaminase (AST) and total protein (TP) while collagen, catalase (CAT), reduced glutathione (GSH), superoxide dismutase (SOD) and malondialdehyde (MDA) levels were assayed in liver tissue homogenate. DMN administration caused significant increases in ALP, AST, HA, ALT, LDH and in liver total collagen content and MDA (p < 0.05) and decreased TP, CAT, GSH and SOD. However 100mg/kg Vernonia amygdalina and Annona muricata leaves attenuated and modulated DMN-induced changes thus giving credence that the leaves possess fibro-suppressant, anti-oxidant and anti-hepatotoxic properties against DMN-induced hepatic fibrosis.